Information and Online Reviews - Andrea Mantovani; Oksana Loginova (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
Online review aggregators, such as TripAdvisor, HotelClub and OpenTable help consumers identify the products and services that best match their preferences. The goal of this study is to understand the impact of online review aggregators on firms and consumers. We adopt Salop's circular city model in which consumers initially do not know the locations of the firms in the product space. The firms decide whether or not to be listed on an online review aggregator's website and choose their prices. When a firm resorts to the aggregator, its location and price become observable to the consumers who visit the website. We consider two different scenarios, depending on the possibility for online firms to offer discounts to the consumers who book online. We show that in equilibrium not all firms will go online – some will remain offline. Online firms attract more customers than their offline counterparts due to reduced mismatch costs, but face a tougher price competition. Comparing the equilibrium prices, profits and the number of firms that go online across the scenarios, we derive interesting conclusions from the private and the social standpoints.
Keywords: C72; D43; D61; L11; L13; M31; 330